Newspaper Coverage of the Bovine Spongiform Encephalopathy Outbreak in the United States: A Content Analysis - Jamie M. King; D. Dwayne Cartmell II; Shelly Sitton (Journal of Applied Communications, 2006)
Objectivity is a hallmark of good journalism. Objective news writing is particularly important when covering agricultural issues. In this study, researchers used the Hayakawa-Lowry news bias categories to examine the objectivity of news coverage of the bovine spongiform encephalopathy (BSE) outbreak that occurred December 23, 2003, in the United States. The study looked at 149 articles published in USA Today, The Washington Post, and The Seattle Times, dating from the day of the outbreak to February 10, 2004, when the USDA concluded its investigation of the outbreak. Based on the findings, the three newspapers studied were more objective than judgmental in their coverage of the outbreak. Although judgment statements were relatively uncommon, the majority of the judgment statements found were negative toward agriculture. Analysis of the level of objectivity for each newspaper revealed that USA Today was the least objective in its coverage; The Seattle Times was the most objective. This study recommends that reporters be encouraged to include more objective sentences in their writing, that journalism and agricultural communications students be educated about the Hayakawa-Lowry news bias categories, that additional research be conducted on media coverage of other agricultural issues, and that the agricultural literacy level of journalists be examined.